Deagregasi Potensi Earthquake Ground Motion pada Jalan Tol untuk Periode Ulang Gempa 1000 Tahun - Sarifah, Fitriana; Ramdani, Yusep; Kurnia Hidayat, Asep (Universitas Sulawesi Barat, 2025)
Port access toll roads, particularly those under the National Strategic Project (PSN), are developed to ease export-import congestion and reduce logistics costs, enhancing industrial competitiveness. This study highlights the importance of earthquake-resistant infrastructure planning through performance-based analysis, which requires time history analysis using recorded ground motions. The objective is to identify appropriate ground motion records for such analysis. The method involves disaggregating average magnitude (M) and distance (R) values to represent seismic sources. Results indicate that M = 6.7 and R = 98 km adequately represent major seismic sources, including Megathrust, Benioff, and Shallow Crustal Faults. The peak ground acceleration (PGA) at bedrock for a 1000-year return period is 0.237 g. The selected ground motion record, with M = 6.7, R = 98 km, and PGA = 0.237 g, was obtained from the USGS database, specifically from the Hilo, HI – USDA Laboratory station (code: NP2818).